Advancing Quality Improvement in Public Health by Exploring CQI in Alabama's Home Visiting Program. Issue 1 (January 2022) - Fifolt, Matthew; Arbour, MaryCatherine; Johnson, Heather H.; Johns, Elisabeth; Preskitt, Julie
Abstract : Continuous Quality Improvement (CQI) is the use of a deliberate and defined improvement process to advance organizational systems. Quality improvement in public health is increasingly widespread, but there are still limited examples of success or descriptions of developmental trajectories for building CQI capacity. The goal of this article is to add to the extant knowledge on the topic by describing one state's implementation of evidence-based CQI in the Maternal, Infant, and Early Childhood Home Visiting program between 2014 and 2019. On the basis of a systematic review of Annual Yearly Progress reports and semistructured key informant interviews, analysis yielded 3 themes that facilitated successful implementation of CQI in Alabama: starting small and building capacity; engaging in continuous and supported learning; and establishing and maintaining a culture of quality. This project demonstrates that CQI can help public health practitioners refine processes and grow capacity to best serve clients' diverse needs. Abstract : Supplemental Digital Content is Available in the Text.